INVESTIGATING THE PATHS OF ROAD INFRASTRUCTURE: ANALYSIS OF THE EFFECTS OF ROADS ON ECONOMIC GROWTH IN PERU - CHANG, VICTOR (2024)
THE OBJECTIVE OF THE RESEARCH IS TO QUANTIFY THE IMPACT OF ROAD INFRASTRUCTURE ON ECONOMIC GROWTH AT THE DEPARTMENTAL LEVEL IN PERU. TO ACHIEVE THIS, A PANEL DATA SET WITH ANNUAL INFORMATION FROM 2010 TO 2022 FOR THE 24 DEPARTMENTS OF PERU IS UTILIZED. A PANEL DATA ERROR CORRECTION MODEL WAS EMPLOYED FOR THIS PURPOSE. THE LONG-TERM ESTIMATION RESULTS REVEAL THAT AN ADDITIONAL 1% INCREASE IN ROAD KILOMETERS LEADS TO A 0.295% INCREASE IN DEPARTMENTAL PER CAPITA GDP. FURTHERMORE, A 1% ADDITIONAL INCREASE IN THE PROPORTION OF PAVED ROAD INFRASTRUCTURE CORRESPONDS TO A 0.339% INCREASE IN DEPARTMENTAL PER CAPITA GDP. ADDITIONALLY, AN INCREASE OF ONE UNIT IN THE NUMBER OF ROAD CONCESSIONS WITHIN THE SAME DEPARTMENT RESULTS IN A 38.9% INCREASE IN DEPARTMENTAL PER CAPITA GDP. © 2024 BY THE AUTHORS.